(untitled) (Revista de Biología Marina y Oceanografía, 2023)
False killer whale (Pseudorca crassidens) is a species of oceanic dolphin that is the only extant representative of the genus Pseudorca. It is found worldwide but mainly frequents tropical regions. This manuscript deals with the first sighting and stranding event recorded of the false killer whale in Mediterranean waters of Bizerte, northern Tunisia. The species has never been reported in the area despite years of collecting anecdotal and scientific information of cetaceans. This report extends previous knowledge of the false killer whale in the Mediterranean Sea.